Pengaruh Model Pembelajaran Multikultural terhadap Kreativitas Seni Siswa Kelas IV pada Mata Pelajaran SBDP - Aljita, Deni; Antosa, Zariul; Munjiatun, Munjiatun (Lembaga Yasin AlSys, 2024)
This research was motivated by the large number of students who were less creative in developing their ideas and ideas. SBdP learning is still dominated by students who have an interest in the arts, so students who are less interested in the arts have difficulty understanding SBdP learning material. The purpose of this study is to describe the influence of multicultural learning models on the artistic creativity of grade IV students in SBdP subjects. The research method used is pre-experiment with a quantitative approach. The design of this study is a one-group Pretest-Posttest Design. This study involved 25 students as research subjects. Researchers carry out learning using a multicultural learning model. Students' artistic creativity is measured through a work reference test in the form of collage works. The results showed that the hypothesis tested using the t test obtained a significance of 0.000 < 0.05 so that Ha was accepted and Ho was rejected. This finding shows that there is an influence of multicultural learning models on the artistic creativity of grade IV students in SBdP subjects.